Feeling objects and fearful symmetries (a review of alone together why we expect more of technology and less from each other by Sherry Turkle, PhD.) - Canlas, Daphne-Tatiana T. (Plaridel, 2014)
Access online through this link: https://www.plarideljournal.org/article/feeling-objects-and-fearful-symmetries-a-review-of-alone-together-why-we-expect-more-of-technology-and-less-from-each-other-by-sherry-turkle-phd